Kebijakan fiskal dan upaya mengatasi disparitas ekonomi perspektif Islam - Agus Waluyo (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2017)
The purpose of this research is to overcome economic disparity in the perspective of Islamic fiscal. Theresearch findings showed that the effort to overcome economic disparity was conducted through economydevelopment that must refer to the base of Islamic philosophy, namely tauhid rububiyah, keadilan,khalifah and tazkiyah. The primary Islamic fiscal should focuse more on distribution of economy fairly.Fair distribution of economy will guarantee the justice amid community, and there is no differencebetween the poor and rich people. The principles of justice guarantee primary need to all society. Besides,each of them is able to fulfill their secondary need. In the context of overcoming economic disparity, itcan be done through optimizing the receiving from instrument of Islamic fiscal policy through strengtheningof regulation, modern and syncron management as well as integration between convensionalfiscal and Islamic fiscal policies.